The Relationship of Knowledge and Attitude towards Handwashing Behavior of Students of SMPN 1 Surakarta and SMPN 6 Surakarta - Abdullah M Azam; . Sumardiyono; Bhisma Murti (Fakultas Kedokteran Universitas Sebelas Maret Surakarta, 2016)
Background: Health status of the child at this time can not be said to be good because of the high frequency of health problems, especially in school children. Problems often arise at school-age children was the lack of concern for personal hygiene. One of them is handwashing behavior before eating and drinking or activities. Therefore, researchers wanted to analyze the relationship between the level of knowledge, attitudes towards Handwashing Behavior with soap in junior high school students. Methods: This study was an observational analytic research with cross sectional approach. The research was conducted in SMPN 1 and SMPN 6 Surakarta. Subjects in this study were drawn from the target population, then reduced to a junior high school student population source (affordable) students of SMPN 1 and SMPN 6 Surakarta. The samples in this study were the second-grade students of SMPN 1 and SMPN 6 contained in the population and meet the inclusion criteria. The number of samples taken was 300 students from the source population of 480 students. Results: The relationship between knowledge level and handwashing behavior with soap (OR = 22.06; CI 95% 12.09 40.24, p=0.000). The relationship between attitude and handwashing behavior with soap (OR = 3.66; CI 95% 2.21 6.06, p=0.000). Conclusion: The students with a good level of knowledge have a greater possibility to do handwashing with soap. The students with a good attitude have a greater possibility to do handwashing with soap. Keywords: Knowledge, Attitude, Handwashing Behavior